Who accepts Savage's axiom now? - Steven J. Humphrey; Nadia-Yasmine Kruse (Theory and Decision, 2023)
We report the results of an experimental test of whether preaching the normative appeal of the sure-thing principle leads decision-makers to make choices that satisfy it. We use Allais-type decision problems to observe the incentive-compatible choices of 147 subjects, which either violate the sure-thing principle or adhere to it. Subjects are presented with normative arguments that support the counterfactual behaviour and then repeat their decisions. We observe violations of the sure-thing principle are robust to its normative justification. This result replicates a famous small-sample observation using hypothetical tasks that was published by Paul Slovic and Amos Tversky almost half a century ago. We argue that this finding is as relevant now as it was then and that their design can be usefully applied to address contemporary issues in behavioural economics.
Keywords: 300; Expected utility theory; Sure-thing principle; Allais Paradox; Normative decision theory